Physiotherapy and occupational therapy interventions for people with benign joint hypermobility syndrome: a systematic review of clinical trials. (May 2014) - Smith, Toby O.; Bacon, Holly; Jerman, Emma; Easton, Vicky; Armon, Kate; Poland, Fiona; Macgregor, Alex J.
Abstract Purpose: This study assessed the literature to determine the efficacy and effectiveness of physiotherapy and occupational therapy interventions in the treatment of people with benign joint hypermobility syndrome (BJHS). Methods: Published literature databases including: AMED, CINAHL, MEDLINE, EMBASE, PubMed and the Cochrane Library, in addition to unpublished databases and trial registries were searched to October 2012. All clinical trials comparing the clinical outcomes of Occupational Therapy and Physiotherapy interventions compared to non-treatment or control intervention for people with BJHS were included. Results: Of the 126 search results, 3 clinical studies satisfied the eligibility criteria. The data provides limited support for the use of wrist/hand splints for school children. While there is some support for exercise-based intervention, there is insufficient research to determine the optimal mode, frequency, dosage or type of exercise which should be delivered. Conclusions: The current evidence-base surrounding Occupational Therapy and Physiotherapy in the management of BJHS is limited in size and quality. There is insufficient research exploring the clinical outcomes of a number of interventions including sensory integration, positioning and posture management and education. Longer term, rigorous multi-centre randomised controlled trials are warranted to begin to assess the clinical and cost-effectiveness of interventions for children and adults with BJHS. Implications for Rehabilitation There is an evidence-base to support clinician's use of proprioceptive-based exercises in adults, and either tailored or generalised physiotherapy regimes for children with BJHS. Clinicians should be cautious when considering the prescription of hand/wrist splints for school age children with BJHS, based on the current research. Until further multi-centre trials are conducted assessing the clinical and cost-effectiveness of interventions for children and adult with BJHS, clinical decision-making should be based on theoretical rather than evidence-based grounds for this population.